2018
DOI: 10.1128/iai.00085-18
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils from Both Susceptible and Resistant Mice Efficiently Kill Opsonized Listeria monocytogenes

Abstract: Inbred mouse strains differ in their susceptibility to infection with the facultative intracellular bacterium , largely due to delayed or deficient innate immune responses. Previous antibody depletion studies suggested that neutrophils (polymorphonuclear leukocytes [PMN]) were particularly important for clearance in the liver, but the ability of PMN from susceptible and resistant mice to directly kill has not been examined. In this study, we showed that PMN infiltrated the livers of BALB/c/By/J (BALB/c) and C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Neutrophils are more effective at L. monocytogenes killing than inflammatory monocytes Phagosomal containment of L. monocytogenes serves little to no purpose if the bacteria are not ultimately killed. Neutrophils and macrophages have been identified as having the primary function of bacteria killing (10,15,36), although there have been some studies that concluded that monocytes also kill during infection (17,33). LAMP-1 is a common lysosomal marker and also a necessary component of the mature phagosome (i.e., the phagolysosome) (37).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Neutrophils are more effective at L. monocytogenes killing than inflammatory monocytes Phagosomal containment of L. monocytogenes serves little to no purpose if the bacteria are not ultimately killed. Neutrophils and macrophages have been identified as having the primary function of bacteria killing (10,15,36), although there have been some studies that concluded that monocytes also kill during infection (17,33). LAMP-1 is a common lysosomal marker and also a necessary component of the mature phagosome (i.e., the phagolysosome) (37).…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils also generated more ROS than monocytes when stimulated. However, this may not necessarily be the manner by which they kill, as a recent finding by Pitts et al (15) concluded that ROS is not required for killing of L. monocytogenes by neutrophils. Mice lacking the gp91 subunit of the NADPH oxidase had previously been demonstrated to be more susceptible to L. monocytogenes (18,19).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations